Critique on Inert Objectification of Nature in Collins’s The Hunger Game - Upadhayay, Toya Nath; Sharma, Kamal (Pragnya Sarathi प्रज्ञा-सारथि, 2025)
The paper critiques Capitol’s perception of nature as an inert object as manipulated in the novel The Hunger Games by Suzanne Collins. Set in the fictional setting of Panem, the story follows Katniss Everdeen, a 16-year-old girl who participates in the brutal game named as ‘Hunger Games’ conducted by the state to remind its citizens of the impact of resistance. The game ‘fight to death’ is annually conducted where one victor is declared after the death of twenty-three tributes. Drawing on the concept of nature as living organism as suggested by Carolyn Merchant, Steven Vogel, and Amitav Ghosh, the paper argues that nature is undefeatable, insurmountable, and indomitable. Merchan’s worries about nature’s objectification, Vogel’s concern on dualism, and Ghosh’s question to inert representation of nature serve the theoretical backup for the study. The paper concludes that the perception of nature as an inert object by the state is critiqued and challenged when the state fails to control its subjects and plants. It is implied that due to mother earth, the survival of ecological selves is possible at a time of hardship.